Critical Studies in Diversity Management Literature: A Review and Synthesis - Gotsis, George (Springer, 2015)
This book critically examines current workplace diversity management practices and explores a nuanced framework for undertaking, supporting, and implementing policies that equally favor all people. It presents critical perspectives that not only elevate respect for differences but also provide insights into the nature and dynamics of differences in view of an inclusive and truly participative organizational environment.